2018
DOI: 10.1126/science.aan1078
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor 1 is a reticulocyte-specific receptor for Plasmodium vivax

Abstract: Plasmodium vivax shows a strict host tropism for reticulocytes. We identify transferrin receptor 1 (TfR1) as the receptor for P. vivax reticulocyte-binding protein 2b (PvRBP2b). The structure of the N-terminal domain of PvRBP2b involved in red blood cell binding was determined, elucidating the molecular basis for TfR1 recognition. TfR1 was validated as the biological target of PvRBP2b engagement by TfR1 expression knockdown analysis. TfR1 mutant cells deficient in PvRBP2b binding were refractory to invasion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
250
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(262 citation statements)
references
References 82 publications
11
250
0
1
Order By: Relevance
“…Table 2 and Table S2 show the individual ranking of all 60 proteins by AUC, note that it is not necessarily the proteins with the highest individual AUC that work best in combination. Table 2, for the top protein PVX_094255 (RBP2b), there were two protein constructs, mapping to different regions of the protein (RBP2b 161-1454 and RBP2b 1986-2653 ), produced in two separate laboratories using different expression and purification methods (30,36). Antibody levels to the two constructs of PVX_094255 (RBP2b 161-1454 and RBP2b 1986-2653 ) were highly correlated (spearman r=0·72, p<0·0001, all cohorts combined) and for this reason the construct that provided lower levels of classification accuracy (region encompassing aa1986-2653) was excluded from the top eight in order to increase the information content provided.…”
Section: Validation Phasementioning
confidence: 99%
“…Table 2 and Table S2 show the individual ranking of all 60 proteins by AUC, note that it is not necessarily the proteins with the highest individual AUC that work best in combination. Table 2, for the top protein PVX_094255 (RBP2b), there were two protein constructs, mapping to different regions of the protein (RBP2b 161-1454 and RBP2b 1986-2653 ), produced in two separate laboratories using different expression and purification methods (30,36). Antibody levels to the two constructs of PVX_094255 (RBP2b 161-1454 and RBP2b 1986-2653 ) were highly correlated (spearman r=0·72, p<0·0001, all cohorts combined) and for this reason the construct that provided lower levels of classification accuracy (region encompassing aa1986-2653) was excluded from the top eight in order to increase the information content provided.…”
Section: Validation Phasementioning
confidence: 99%
“…Given a wide range of results pointing to P. vivax preference for infection of reticulocytes (40-48) and the apparent low, variable expression Fy protein on Fy*B ES /*B ES pbRBC, we postulated that this expression pattern may reflect the lower and declining stages of Fy expression on aging pbRBC. Further recent evidence from murine studies showing that the Fy protein is expressed at higher levels on pro-erythroblasts and normoblasts, compared to mature RBC (49), suggesting that we should investigated Fy expression in erythroid precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial studies focused on peripheral blood RBCs (pbRBC), showed that Fy expression on Fy-negative pbRBC was periodically positive and that these RBC could interact with rPvDBPII at levels similar to RBC from FY*A/*A people. Well aware that numerous studies point to P. vivax preference for infection of reticulocytes (40, 42-48), we were interested to study Fy expression across a broader time frame of erythroid development. Recent evidence from murine and human studies shows higher levels of Fy protein expression on pro-erythroblasts and normoblasts, compared to mature RBC (46, 49).…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that transgenic P. knowlesi parasites using PvDBP for invasion have no such restriction, invading human RBCs (which typically contain less than 0.5% reticulocytes) with the same efficiency as those expressing PkDBP – thus providing compelling evidence that PvDBP plays no role in the reticulocyte tropism. Further, recent work determining that PvRBP2b, which lacks an orthologue in P. knowlesi , binds to the reticulocyte specific marker CD71 (50) further asserts the RBPs as the key to reticulocyte tropism. Importantly, the ability to compare and contrast activity of Pk/Pv DBP family members in parasitological assays will provide a vital new tool to test hypotheses and models arising from studies that have until now relied on assays using recombinant protein fragments.…”
Section: Discussionmentioning
confidence: 99%